Climate Patterns in the World’s Longest History of Storm-Erosivity: The Arno River Basin, Italy, 1000–2019 CE - Diodato, Nazzareno; Ljungqvist, Fredrik Charpentier; Bellocchi, Gianni (Frontiers in Earth Science, 2021)
Rainfall erosivity causes considerable environmental damage, with economic losses, worldwide and are driven by diluvial storms. However, the long-term evolution of erosive forcing (over centennial to millennial time-scales) remains essentially unknown. Using a rainfall erosivity model (REMARB), this study simulates the variability of rainfall erosivity in Arno River Basin (ARB), Italy, a Mediterranean fluvial basin, for the period 1000–2019 CE resulting in the world’s longest time-series of erosivity. The annual estimates show a noticeable and increasing variability of rainfall erosivity during the Little Ice Age (~1250–1849), especially after c. 1490, until the end of 18th century. During this cold period, erosive forcing reached ~1600 MJ mm hm-2 h-1 yr-1 once every four years, and ~3000 MJ mm hm-2 h-1 yr-1 once every 20 years. The extremes of rainfall erosivity (the 98th percentile) followed a similar increasing trend, with an acceleration of the hydrological hazard (erosivity per unit of rainfall) during the 20th century. The comparison of REMARB output with the sediment yield of the basin (1951–2010) confirmed the model’s ability to predict geomorphological effects in the ARB. Thus, our methodology could be applied to simulate erosivity in environmentally similar basins. A relationship has been identified between the Atlantic Multidecadal Variation and erosivity patterns, suggesting a role of North Atlantic circulation dynamics on the hydrology of central Italy’s fluvial basins.